Water - Spatial Network Pricing - Yuri Yegorov (European Regional Science Association (ERSA), 2005)
The paper addresses an important issue of pricing mechanisms is spatially distributed systems with losses, with an application to water supply system. When losses from delivery are high, the asymmetry of spatial location of consumers plays an important role, which is captured by the model. The goal is to compare the efficiency from alternative market structures for water supply. The model can be applied for channels aimed on water redistribution. In particular, the model can be relevant for analysing different market structures, equilibrium water pricing and efficiency for the planned channels. Potential application can be planned channel between river Ebro (Spain) and communities Valencia and Murcia. While this paper is purely theoretical, it addresses the issues that are still little understood at administrative level. Water market as described is a necessity, but it will not emerge spontaneously and it requires appropriate legislative preparation. Mathematical model is designed in terms of densities and flows of corresponding economic variables.
Keywords: 330